IMF Survey, Volume 36 Issue 10. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 2007)
IMF work agenda; IMF exchange rate advice; Asia's trade pacts; Central Asia: economic cooperation; Cameroon after debt relief; spread of Austrian banks; conference on financial soundness indicators; Caruana on shifting roles in financial globalization.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet